2011
DOI: 10.29333/ejgm/82722
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of the Pubic Louse Pthirus Pubis in Two Patients Complaining from Tick Infestation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In Internet queries we observed that the name corporis is still widely used and that many scientists are uncertain about which one should be the correct name for the human body louse. This problem is well illustrated by the example of three publications from 2010 and 2011: Abdel-Ghaffar et al ( 2010) used Pediculus humanus corporis and Pediculus humanus capitis, Cueto & Picollo (2010) used Pediculus humanus humanus and Pediculus humanus capitis, and Beytur et al (2011) used Pediculus corporis and Pediculus capitis. Furthermore, a query for Pediculus corporis in May 2011 yielded more than 5,000 hits in Google Scholar.…”
mentioning
confidence: 99%
“…In Internet queries we observed that the name corporis is still widely used and that many scientists are uncertain about which one should be the correct name for the human body louse. This problem is well illustrated by the example of three publications from 2010 and 2011: Abdel-Ghaffar et al ( 2010) used Pediculus humanus corporis and Pediculus humanus capitis, Cueto & Picollo (2010) used Pediculus humanus humanus and Pediculus humanus capitis, and Beytur et al (2011) used Pediculus corporis and Pediculus capitis. Furthermore, a query for Pediculus corporis in May 2011 yielded more than 5,000 hits in Google Scholar.…”
mentioning
confidence: 99%
“…In Internet queries we observed that the name corporis is still widely used and that many scientists are uncertain about which one should be the correct name for the human body louse. This problem is well illustrated by the example of three publications from 2010 and 2011: Abdel-Ghaffar et al ( 2010) used Pediculus humanus corporis and Pediculus humanus capitis, Cueto & Picollo (2010) used Pediculus humanus humanus and Pediculus humanus capitis, and Beytur et al (2011) used Pediculus corporis and Pediculus capitis. Furthermore, a query for Pediculus corporis in May 2011 yielded more than 5,000 hits in Google Scholar.…”
mentioning
confidence: 99%